Measuring and predicting teamwork quality in virtual project teams - Markus Behn; Gilbert Silvius (International Journal of Information Systems and Project Management)
More and more members of project organizations collaborate in virtual teams. Due to globalization and more recently driven by the impact of the Covid-19 pandemic, the number of virtual project team members grew significantly, and many leaders look for key factors which allow virtual teams to reach a higher level of Teamwork Quality. This article summarizes previous investigations to develop a measuring instrument for both Teamwork Quality and potential predictors. Based on a literature review a conceptual model with 30 salient items measuring ten latent predictors as well as one latent concept for Teamwork Quality has been developed and transformed into a survey. The questionnaire was shared online and completed by 211 members of virtual project teams. Afterwards an Explorative Factor Analysis as well as a Reliability Analysis have been performed to explore the structure of the items. The result suggested one dependent measure for Teamwork Quality in virtual project teams and three latent predictors. These factors have been included into a Structural Equation Model and have been supported by a Confirmatory Factor Analysis. The steps described led to three factors (Personal Commitment, Team Balance & Mutual Support, Result Orientation) that have an influence on the latent variable “Willingness to succeed”.